Perancangan Multimedia Pembelajaran Bimbingan TIK Kelas XII Menggunakan Autoplay Media Studio di SMAN1 Padang Sago - Furqan, Muhammad; Efriyanti, Liza; Sesmiarni, Zulfani; Zakir, Supratman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted from the existence of problems that have been observed by the author at SMAN 1 Padang Sago where the problems were found. whenthe learning process takes place the media presented is still in the form of microsoft word which is displayed through an LCD projector, and has not used interesting media to be presented to students. This is to produce a multimedia design that supports ICT Guidance learning using Autoplay Media Studio that is valid, practical and effective.The method used in this research is the Luther-Sutopo version of the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept (conception), design (design), collecting material (material collection), assembly (making), testing (testing) and distribution (distribution). And there are three product tests carried out in this study, namely the validity test given to lecturers who are field experts or field experts, practicality tests carried out by teachers of the subject of ICT guidance and effectiveness tests given to two teachers in the field of study and ten students at SMAN. 1 Padang Sago class XII.Based on the product test results that have been carried out by the author of the validity test, the average value is 0.93 which is declared valid, and for the practicality test, the average value is 0.97 which is declared practical and for the effectiveness test, the average value is obtained.the average is 0.83 which is declared effective.